Event-related fMRI at 7T reveals overlapping cortical representations for adjacent fingertips in S1 of individual subjects - Besle, Julien; Sánchez-Panchuelo, Rosa-Maria; Bowtell, Richard; Francis, Susan; Schluppeck, Denis (Human brain mapping, 2014)
Recent fMRI studies of the human primary somatosensory cortex have been able to differentiate the cortical representations of different fingertips at a single‐subject level. These studies did not, however, investigate the expected overlap in cortical activation due to the stimulation of different fingers. Here, we used an event‐related design in six subjects at 7 Tesla to explore the overlap in cortical responses elicited in S1 by vibrotactile stimulation of the five fingertips. We found that all parts of S1 show some degree of spatial overlap between the cortical representations of adjacent or even nonadjacent fingertips. In S1, the posterior bank of the central sulcus showed less overlap than regions in the post‐central gyrus, which responded to up to five fingertips. The functional properties of these two areas are consistent with the known layout of cytoarchitectonically defined subareas, and we speculate that they correspond to subarea 3b (S1 proper) and subarea 1, respectively. In contrast with previous fMRI studies, however, we did not observe discrete activation clusters that could unequivocally be attributed to different subareas of S1. Venous maps based on T2*‐weighted structural images suggest that the observed overlap is not driven by extra‐vascular contributions from large veins. Hum Brain Mapp 35:2027–2043, 2014. © 2013 The Authors Human Brain Mapping published by Wiley Periodicals, Inc.